2021
DOI: 10.1007/s10926-021-09992-5
|View full text |Cite
|
Sign up to set email alerts
|

First Contact Practitioners’ (FCPs) and General Practitioners’ Perceptions Towards FCPs Delivering Vocational Advice to Patients with Musculoskeletal Conditions: A Qualitative Investigation of the Implementation Potential of the I-SWAP Initiative

Abstract: Purpose Musculoskeletal (MSK) pain is a common cause of work absence. The recent SWAP (Study of Work And Pain) randomised controlled trial (RCT) found that a brief vocational advice service for primary care patients with MSK pain led to fewer days’ work absence and provided good return-on-investment. The I-SWAP (Implementation of the Study of Work And Pain) initiative aimed to deliver an implementation test-bed of the SWAP vocational advice intervention with First Contact Practitioners (FCP). This entailed ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“… O’Brien et al (2008) reported that patients often sought advice from their GP about work-related issues, but they perceived GPs did not have sufficient time or knowledge to address these issues adequately. We observed similar concerns in a recent study exploring the potential for First Contact Practitioners (FCPs) to deliver vocational advice to patients absent from work with musculoskeletal pain ( Saunders et al, 2022 ). The FCPs cited lack of time to explore the barriers and obstacles to patients returning-to-work in depth, and lack of confidence in addressing some of the psychosocial issues underlying work absence.…”
Section: Discussionsupporting
confidence: 62%
“… O’Brien et al (2008) reported that patients often sought advice from their GP about work-related issues, but they perceived GPs did not have sufficient time or knowledge to address these issues adequately. We observed similar concerns in a recent study exploring the potential for First Contact Practitioners (FCPs) to deliver vocational advice to patients absent from work with musculoskeletal pain ( Saunders et al, 2022 ). The FCPs cited lack of time to explore the barriers and obstacles to patients returning-to-work in depth, and lack of confidence in addressing some of the psychosocial issues underlying work absence.…”
Section: Discussionsupporting
confidence: 62%
“…Patel et al [ 102 ] Australia Mixed-methods process evaluation Primary care CVD management Prospective 31. Saunders et al [ 103 ] UK Qualitative Primary care Musculoskeletal pain Retrospective 32. Schnabel et al [ 104 ] UK Qualitative Stroke services Augmented arm rehabilitation, supported self-management after stroke Prospective 33.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the operationalisation of the sub-constructs, while just over half of the studies ( n = 22) [ 36 , 68 72 , 75 , 78 , 85 – 87 , 95 , 99 101 , 103 , 104 , 108 111 , 113 , 114 ] did not specify the use of any sub-constructs, nearly 30% of studies ( n = 12) [ 73 , 74 , 76 , 77 , 80 84 , 89 91 , 93 , 97 , 102 , 105 , 112 ] explicate their use of all 16 and use among the remaining studies (19%, n = 8) [ 79 , 88 , 92 , 94 , 96 , 98 , 106 , 107 ] varied. Figure 2 further illustrates the frequency of sub-construct use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have identified various perspectives on the roles and responsibilities as well as barriers at systemic and organisational levels that cannot be addressed through GP training courses alone [ 35 ]. Ultimately, this leads to questions about who will be best suited to help the patients stay-at-work [ 36 ], and how they are best incentivised [ 35 ]. In the end, it matters more that patients receive the best possible help in maintaining a life with high social participation including participation in work life than who is involved in the management.…”
Section: Discussionmentioning
confidence: 99%